Designing for Active Place Presence at Home: The Hole in Space Design Experiment - Sellen, Abigail (Proceedings of DIS, 2016)
Technological support for augmenting the relationship that people establish with remote places has been studied fairly little as the primary focus in telepresence studies is the connection between people. This paper addresses the design challenge for supporting ‘active place presence’ at home. A prototype, Hole in Space, was created to explore the design challenge. A longitudinal study of how an urban couple appropriated the prototype was conducted over the duration of seven months. The paper elaborates on how the Web-mediated design influenced place presence and outlines several aspects that need to be considered when designing for active place presence at home.